Rancang Bangun Sistem Informasi Penggajian Di PT. Big Surabaya - Primatondhano, Yuditya; Tanuwijaya, Haryanto; Mastan, Ignatius Adrian (Jurnal JSIKA, 2012)
PT. BIG Surabaya is a multi-company which has the department include Banquet and Restaurant, T-Bar, Office Park, Regency. Implementation of operational activities at PT. BIG Surabaya still using manual systems. Analysis and design of existing can not help solve the problems in PT. BIG Surabaya. Preparation of employee payroll information system applications are expected to assist in realizing komputerasisasi system and assist the operations of PT BIG Surabaya. Keyword:  PT. BIG Surabaya, payroll information system